Experimental line strengths of the 5ν2 band of H232S in comparison with the results of "variational" calculation and HITRAN database. (March 2020) - Ulenikov, O.N.; Bekhtereva, E.S.; Gromova, O.V.; Raspopova, N.I.; Belova, A.S.; Maul, C.; Sydow, C.; Bauerecker, S.
Highlights: Experimental line strengths are determined for the 5v2 band of H2S. Effective dipole moment parameters of the 5v2 band are obtained. Comparison with the HITRAN and the results of "variational" calculations are made. Abstract: The strengths of 176 transitions of the 5 ν 2 band of H 2 32 S were experimentally recorded with a Bruker IFS 125HR Fourier transform infrared spectrometer and theoretically analyzed. The seven effective dipole moment parameters of this band were obtained from the weighted fit which reproduce the initial experimental line strengths with the d rms = 3.4%. A comparison of the obtained results with the results of variational calculation and HITRAN data is presented.